2019
DOI: 10.1039/c9np00018f
|View full text |Cite
|
Sign up to set email alerts
|

Computational prediction of chiroptical properties in structure elucidation of natural products

Abstract: A tutorial review aimed to introduce natural product chemists to the predictions of natural product configurations by ECD and OR calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 106 publications
1
90
0
Order By: Relevance
“…For the configurational assignment of 1 , the solution TDDFT‐ECD method was applied on the arbitrarily chosen ( S ) stereoisomer . Since 1 is conformationally flexible and the relative orientation of the three aromatic chromophores produced by rotation along the C‐3‐C‐13 biaryl axis and the sigma bonds of the C‐6 chirality center is expected to be fundamental for the sign and shape of the ECD transitions, a thorough conformational search is inevitable . Consequently, the initial 37 MMFF conformers of ( S )‐ 1 were reoptimized at both the ωB97X/TZVP PCM/MeCN and the SOGGA11‐X/TZVP SMD/MeCN levels of theory .…”
Section: Resultsmentioning
confidence: 99%
“…For the configurational assignment of 1 , the solution TDDFT‐ECD method was applied on the arbitrarily chosen ( S ) stereoisomer . Since 1 is conformationally flexible and the relative orientation of the three aromatic chromophores produced by rotation along the C‐3‐C‐13 biaryl axis and the sigma bonds of the C‐6 chirality center is expected to be fundamental for the sign and shape of the ECD transitions, a thorough conformational search is inevitable . Consequently, the initial 37 MMFF conformers of ( S )‐ 1 were reoptimized at both the ωB97X/TZVP PCM/MeCN and the SOGGA11‐X/TZVP SMD/MeCN levels of theory .…”
Section: Resultsmentioning
confidence: 99%
“…We, as well as other authors, demonstrated that most of the traditional empirical correlation rules are inadequate and often incorrect and may lead to wrong conclusions [ 57 , 58 , 59 ]. Solving the Rosenfeld equation of optically active electron transitions, with the use of modern theoretical methods, mostly the DFT-based one is an alternative to the empirical rules [ 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The absolute configuration of compound 1 was determined on the basis of its predicted optical rotation (OR). DFT prediction of OR is a valuable, although not as general, alternative to ECD for determining the absolute configuration of natural products, and can be reliably used for this purpose provided that (i) the magnitude of the measured OR is not close to zero and (ii) the sign of the calculated OR is the same for all, or at least for most conformers [28]. The OR of compound 1 was predicted at the B3LYP/TZVP/PCM(MeOH) level of theory; the calculated [α] D (as the Boltzmann average of individual conformers) was -104, compared to the experimental value -56.…”
Section: Structure Elucidationmentioning
confidence: 99%